Palladium-Catalyzed [1,3]-O-to-N Rearrangement of Allylic Imidates - Kuroda, Yusuke (Synlett, 2021)
The rearrangement of allylic imidates is a powerful transformation for the synthesis of allylic amines. Whereas the [3,3]-rearrangement has long been established as the Overman rearrangement, the corresponding [1,3]-rearrangement is rare. Here, we report a novel strategy for the [1,3]-rearrangement of imidates based on the oxidative addition of a palladium(0) catalyst to an allylic imidate. Structurally distinct allylic amides could be synthesized under mild and base-free conditions.
Keywords: palladium catalysis; allylic substitution; [1,3]-rearrangement; imidates; amides